Korelasinilai dan Moral Agama Peserta Didik dengan Hubungan Sosial Teman Sebaya - Abdul Sahib (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
ABSTRACT The purpose of this study was to study the moral values and religious religion of students at SMPN 1 Curup with peer social relations. This research is in the form of quantitative research with 80 respondents from IX grade students of SMPN 1 Curup. This study uses a descriptive experimental analysis approach that aims to determine the effect of the research variables. Based on the research findings can be known, after testing the hypothesis in the calculation of Pearson correlation (correlation product moment) to get the results of r = 0.483014809, it can be concluded that there is a correlation between moral values and religion on peer social relations. The conclusion of this study is that religious values and morals determine the quality of peers' social relationships in adolescents. Keywords: Religious Moral, Social Relations, peers